THE INFLUENCE OF LEE-CARTER STOCHASTIC MORTALITY ASSUMPTION AND GOMPERTZ DETERMINISTIC MORTALITY ASSUMPTION TO THE VALUES OF ANNUITIES, BENEFITS, AND PREMIUMS - NUR FAHIRAH SUDDING (NIM : 20811003); Pembimbing : Dr. M. Syamsuddin, FAUZIAH
Actuarial calculations to the values of annuities, beneﬁts , and premiums are inﬂuenced by mortality factor or the probability someone would die for each year. The calculations can be calculated by using actuarial functions on mortality tables or mortality law. One of the deterministic mortality inventor who quite famous, namely Gompertz. And during the last decades, stochastic methods have been developed, one of including is Lee-Carter methods. In this thesis, the author will compare probablities by applying both assumptions, in order to see the inﬂuence on the values of annuities, beneﬁts , and premiums. It is found that the values of annuities, beneﬁts, and premiums by using Gompertz method only provides result for one year, while Lee-Carter method provides diﬀerent result each year, by following trend of deaths each year. And for the value of deaths probabilities by using Gompertz method provides greater value than Lee-Carter method for ages 24-68, which have an impact on the values of premium and beneﬁts also greater.